1992
DOI: 10.1073/pnas.89.18.8716
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of damage to photosystems I and II in a cyanobacterium lacking detectable iron superoxide dismutase activity.

Abstract: The enzyme superoxide dismutase is ubiquitous in aerobic organisms where it plays a major role in alleviating oxygen-radical toxicity. An insertion mutation introduced into the iron superoxide dismutase locus (designated sodE) of the cyanobacterium Synechococcus sp. PCC 7942 created a mutant strain devoid of detectable iron superoxide dismutase activity. Both wild-type and mutant strains exhibited similar photosynthetic activity and viability when grown with 17 jmolm-2-s'1 illumination in liquid culture supple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 20 publications
3
64
0
Order By: Relevance
“…In contrast, the mRNA level for a DnaJ-like protein of the HSP40 family was substantially decreased. The transcript concentration for the Fe superoxide dismutase (Herbert et al, 1992;Samson et al, 1994) was found to be lower in Fedepleted cells than in Fe-sufficient cells. Altogether, these findings reveal that Fe-independent detoxification systems compensate in part the Fe-dependent parts of the cellular detoxification system.…”
Section: Transcripts Of Genes Encoding General Stress Proteinsmentioning
confidence: 97%
“…In contrast, the mRNA level for a DnaJ-like protein of the HSP40 family was substantially decreased. The transcript concentration for the Fe superoxide dismutase (Herbert et al, 1992;Samson et al, 1994) was found to be lower in Fedepleted cells than in Fe-sufficient cells. Altogether, these findings reveal that Fe-independent detoxification systems compensate in part the Fe-dependent parts of the cellular detoxification system.…”
Section: Transcripts Of Genes Encoding General Stress Proteinsmentioning
confidence: 97%
“…Thus, the increased PSI content in the mutants may result in much more production of reactive species of oxygen, which might account for the loss of viability of the mutants under the prolonged stress of HL. It is widely accepted that electrons generated from PSI react with oxygen to produce the superoxide anions, which are mainly scavenged by superoxide dismutase and ascorbate peroxidase (Asada, 1992;Herbert et al, 1992). It was recently demonstrated that irreversible photoinhibition of PSI occurs at its acceptor side in chilling-sensitive plants under chilling stress, possibly due to a loss of protection against the reactive species of oxygen (Sonoike and Terashima, 1994;Sonoike, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that CSD2 is essential for protecting the chloroplasts in higher plants from photooxidative damage. In the unicellular cyanobacterium Synechococcus, which possesses two SODs, MnSOD in the thylakoids and FeSOD in the cytosol, a mutant strain lacking FeSOD is sensitive to photooxidative stress, and its PSI complex is inactivated (Herbert et al, 1992;Samson et al, 1994;Thomas et al, 1998). However, the role of FeSOD isozymes in maintaining chloroplast function has not yet been documented.…”
Section: Introductionmentioning
confidence: 99%